2013
DOI: 10.1083/jcb.201211141
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of Greatwall kinase nuclear localization facilitates mitotic progression

Abstract: Greatwall kinase relocation from the nucleus to the cytoplasm is required at mitotic entry and is mediated by a phosphorylation-dependent mechanism targeting its central region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 50 publications
6
70
1
Order By: Relevance
“…This finding is in agreement with previous studies in human and Drosophila that reported nuclear export of Gwl before nuclear membrane breakdown. 15,20 However, distinct from the previous study that suggested a requirement of Gwl kinase activity for its nuclear export, 20 we found a similar pattern of nucleocytoplasmic relocalization for G41S Gwl prior to mitotic entry (Fig. 4B).…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celcontrasting
confidence: 52%
See 4 more Smart Citations
“…This finding is in agreement with previous studies in human and Drosophila that reported nuclear export of Gwl before nuclear membrane breakdown. 15,20 However, distinct from the previous study that suggested a requirement of Gwl kinase activity for its nuclear export, 20 we found a similar pattern of nucleocytoplasmic relocalization for G41S Gwl prior to mitotic entry (Fig. 4B).…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celcontrasting
confidence: 52%
“…15,20 We also observed in Xenopus cells that nuclear Gwl started to diffuse into cytoplasm before centrosomes reached opposite positions. While it remained unclear how this nucleocytoplasmic translocation of Gwl may contribute to the regulation of mitotic entry, previous studies indicated that the translocation was dependent on Gwl phosphorylation by CDK1, and possibly also Plk1.…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celmentioning
confidence: 73%
See 3 more Smart Citations